HIV-1 protease mutations and inhibitor modifications monitored on a series of complexes. Structural basis for the effect of the A71V mutation on the active site - Skalova, Tereza; Dohnalek, Jan; Duskova, Jarmila; Petrokova, Hana; Hradílek, Martin; Soucek, Milan; Konvalinka, Jan; Hasek, Jindrich (Journal of medicinal chemistry, 2006)
Two new X-ray structures of an HIV-1 protease mutant (A71V, V82T, I84V) in complex with inhibitors SE and SQ, pseudotetrapeptide inhibitors with an acyclic S-hydroxyethylamine isostere, were determined. Comparison of eight structures exploring the binding of four similar inhibitors--SE, SQ (S-hydroxyethylamine isostere), OE (ethyleneamine), and QF34 (hydroxyethylene)--to wild-type and A71V/V82T/I84V HIV-1 protease elucidates the principles of altered interaction with changing conditions. The A71V mutation, which is distant from the active site, causes changes in the structure of the enzyme detectable by the means of X-ray structure analysis, and a route of propagation of the effect toward the active site is proposed.
Keywords: inhibitory HIV-proteasy; vodíková vazba; ethanolaminy; Models, Molecular; Oligopeptides; ligandy; HIV Protease Inhibitors; krystalografie rentgenová; Ethanolamines; oligopeptidy; mutace; Hydrogen Bonding; Crystallography, X-Ray; Ligands; molekulární modely; Mutation; vztahy mezi strukturou a aktivitou; Binding Sites; HIV Protease; HIV-proteasa; molekulární struktura; Structure-Activity Relationship; vazebná místa; Molecular Structure